Go Long or Short in Pyramids? : News from the Egyptian Stock Market - Massa, Isabella (IMF Working Papers; Working Paper, 2007)
Similar to other emerging economies, the Egyptian stock market has recently experienced a remarkable run-up but also a major downturn. This paper analyzes the stock market from two angles. First, it compares the performance of the major stock price index with its underlying fundamentals. Second, it explores the relationship between the Egyptian and other stock markets. The paper finds that (i) there is some evidence against a stable relationship between the Egyptian index and its fundamental value; and (ii) short-term correlations and long-term cointegrating relations provide conflicting signals on the value of Egyptian stocks as a means of diversification.